PENERAPAN METODE EXPLORE ASK READ TELL HARVEST (EARTH) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA DI SEKOLAH DASAR - Citra Wibisono, Wulandari; Hana Pebriana, Putri; Aprinawati, Iis; Yandri Kusuma, Yanti; Fadhilaturrahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the low reading comprehension ability of students in Indonesian lessons in class V UPT SDN 016 Bangkinang Kota. One solution to overcome this problem is to use the explore ask read tell harvest (EARTH) method. This study aims to improve reading comprehension skills using the explore ask read tell harvest (EARTH) method in grade V students of UPT 016 Bangkinang Kota. This research method is Classroom Action Research (PTK) which is carried out in two cycles consisting of two meetings and four stages, namely implementation planning, observation and reflection. The time of this research will be carried out in July 2024. The subject of this study is class V students of UPT 016 Bangkinang Kota consisting of 21 students, there are 10 male students and 11 female student. The data collection method uses observation techniques, and documentation techniques. The results of the study show that using the explore ask read tell harvest (EARTH) method can improve students' reading comprehension. This is shown by the results of observation in each cycle I of meeting I from 21 students, it is known that the reading comprehension ability of students who are included in the category of complete reached 12 people or 57% and in the first cycle of meeting II there were 14 people or 67%. Then in the second cycle of the first meeting there were 15 people or 71% who experienced completeness and in the second cycle the second meeting increased to 18 people or 87%. Through the application of the explore ask read tell harvest (EARTH) method in improving the reading comprehension ability of grade V students of UPT SDN 016 Bangkinang Kota.